A New Electric Accessory Drive System for Hybrid Electric Vehicles - Mese, E.; Yasa, Y.; Akca, H.; Aydeniz, M. G.; Garip, M. (IEEE, 2012)
This paper presents a new electric accessory drive system for hybrid electric vehicles. The system offers cost and space advantages. In this concept, dual winding electric machine with simultaneous motor and generator functions is used. The electric machine provides power for all accessory loads such as steering pump, compressors, and 12V loads. If the engine is on, accessory loads are driven by engine through a belt like conventional vehicle. If the engine is off, electric machine's motoring action starts and provides mechanical power to accessory loads. Simultaneously, the generator windings provide power for 12 V loads. Converter options for generator were also investigated and preliminary experimental results were presented.
Keywords: Permanent Magnet Synchronous Machine; Concentrated Winding; Dual Winding Electric Machine; Electric accessory drive system; Hybrid Electrical Vehicle Application; Engineering